Innovative Solar Integration: Developing an Efficient Energy System for Electric Vehicles - Thangavelu, Raja; Manikandan, Kadirvel; Govindan, Raja; Babu, N. Sreenivasa (Journal of Neonatal Surgery, 2025)
The use of solar panels in vehicles, especially buses and automobiles, offers a promising future for green transportation through the direct utilization of sunlight to power or supplement electrical systems, thus lessening dependence on fossil fuels and greenhouse gas emissions. This vehicle-integrated photovoltaic (VIPV) system, which uses specialized, light-weight solar cells on vehicle surfaces, can increase fuel efficiency, increase driving range, and decrease operating costs for both conventional and electric vehicles. Although considerations like solar panel size, efficiency, and vehicle design compatibility are important, solar technology advancements are making way for successful implementation. In addition to environmental advantages, solar-powered cars hold the promise of energy self-sufficiency and cleaner air; yet, factors such as the variability of solar power and upfront capital require efficient energy storage technologies and ongoing technological advancements to make their general potential for a cleaner transportation industry possible.